Night of the Ninjas - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1995)
The magic tree house takes Jack and Annie back in time to feudal Japan where the siblings learn about the ways of the ninja.
Book Links (A.L.A.).
Book Links (A.L.A.), November 1997.
3.6
3-6
Keywords: Annie (Fictitious character : Osborne) -- Juvenile fiction; Jack (Fictitious character : Osborne) -- Juvenile fiction; Magic -- Juvenile fiction; Ninja -- Juvenile fiction; Time travel -- Juvenile fiction; Tree houses -- Juvenile fiction; Annie (Fictitious character : Osborne) -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Magic -- Fiction; Ninja -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Magic -- Fiction; Ninja -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Japan -- Juvenile fiction; Japan -- Fiction; Japan -- Fiction